Vulkanostratigrafi dan Implikasi Terhadap Tanah Longsor Daerah Serang dan Sekitarnya, Kecamatan Salawu, Kabupaten Tasikmalaya, Provinsi Jawa Barat - Rizqi, Al Hussein Flowers; Aprilia, Adinda; Tedja Trisnaning, Paramitha (Institut Teknologi Nasional Yogyakarta, 2024)
The research area is administratively located in the Serang area and its surroundings, Salawu District, Tasikmalaya Regency, West Java Province. Geographically, the research area is at coordinates 7°20'24